Analisis Pelanggaran Hukum Ketenagakerjaan Yang Dilakukan Oleh Pt. Alpen Food Industry Terhadap Karyawan - Redhytta Putri Wulandari; Muhamad Rizal; Sari Usih Natari (Lembaga Pengembangan Kinerja Dosen, 2023)
Alpen Food Industry, the most renowned ice cream manufacturer in Indonesia, boasts a widespread presence with 80,000 outlets across the nation. However, beneath the surface of PT. Alpen Food Industry's success, having once been honored with the Excellent Brand Award, allegations of labor law violations have emerged, leading to protests by its employees. In an effort to fight for their rights, the workers staged a two-week strike. The strike was initiated to advocate for their entitlements. Additionally, PT. Alpen Food Industry is accused of unilaterally implementing Termination of Employment (PHK) procedures. Nonetheless, the company refutes these allegations, asserting that they conducted the PHK in accordance with existing protocols and guidelines. They claim to have sent two separate Call Letters to the workers, which went unanswered, and argue that this inaction is tantamount to resignation based on the prevailing guidelines. This research employed a qualitative approach, gathering data through literature review methods involving various sources such as journals, news articles, and websites. The author then drew conclusions based on the obtained data. The research findings suggest that the dispute arose primarily from a lack of communication between the workers and the employer.